STRATEGI KOMUNIKASI CORPORATE SOCIAL RESPONSIBILITY (CSR) DI PT PLN (PERSERO) DISTRIBUSI JAWA TENGAH DAN DIY TAHUN 2013 - 2014 - Octaviana, Shoraya Lolyta (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2016)
Abstract : Corporate social responsibility has become a global issue in the community and the company. CSR programs conducted by PT PLN (Persero) Distribution Regional Central Java and Yogyakarta in the areas specially for Education, Health, Community Empowerment and Environmental Conservation has been right on target. Corporate Social Responsibility program targets, among others, that people are more concerned with the condition of the PLN, and for good imaging PLN by society. Communication strategy to the public that are used in the dissemination using print media such as newspapers and magazines nationally and locally. Electronic media using television and radio in Central Java and Yogyakarta and national, also use social media such as Facebook and Twitter.Keywords : Strategic Communication, Corporate Social Responsibility.